plz solve this by long division
Attachments:
![](https://hi-static.z-dn.net/files/dc6/c0cccd4901095663cc2a34ccb920e09b.jpg)
Answers
Answered by
1
x^3-2x^2-x+2
put x=1
1^3-2×1^2-1+2
=0
1 is zero is p(x).
hence x-1 is factor of p(x).
by long division,we get,
p(x)=(x-1)(x^2-x-2)
=(x-1)(x-2)(x+1)
put x=1
1^3-2×1^2-1+2
=0
1 is zero is p(x).
hence x-1 is factor of p(x).
by long division,we get,
p(x)=(x-1)(x^2-x-2)
=(x-1)(x-2)(x+1)
Answered by
0
Khud Karrrrrrrrrrrrrrrrrrrrrrrrrrr
Similar questions
Social Sciences,
8 months ago
English,
8 months ago
Math,
8 months ago
Math,
1 year ago
History,
1 year ago
English,
1 year ago
Biology,
1 year ago
Social Sciences,
1 year ago